Menelisik Pola Berpikir Koruptif Para Pedagang Licik: Sebuah Tinjauan Teologis atas Teks Amos 8:4-8 - Siang Suk Hauw; Bernadus Dirgaprimawan (Studia Philosophica et Theologica, 2023)
This article aims at investigating the craftiness of wicked merchants as illustrated in the Book of Amos chapter 8:4-8. By employing a close reading as a chosen approach to that particular text, it will be discussed how corruptive minds of those merchants preceed their unjust acts. A close reading is a synchronic approach that Mfocuses on every detail of the story, in particular on the plot and the characterization. Every word coming from the mouth of a character, enhanced with his action, carries significant weight and thus contributes to the fuller description of his personality. This article, therefore, is interested in examining the inner thought of these cunning merchants. In chapter 8:4-8, they deliberately set the poor in a trap, even when these miserable people cannot afford to buy the refuse of the wheat. Then, as calculated by these evil merchants, the poor have to sell themselves in order to have something to eat. This article also aims at showing the reader that for the author of the Book of Amos, corruptive minds of those merchants degrade human dignity. Such a corruptive mentality leads to a larger social injustice. It seems that this author wants remind the reader to be cautious whenever a corruptive mind begins to occupy one’s thought.